MULTIOBJECTIVES ANALYSIS OF WASTEWATER MANAGEMENT SYSTEM IN TAPIOCA STARCH INDUSTRY: CASE STUDY - CIAMIS DISTRICT, WEST JAVA (Analisis Multiobyektif sistem Pengelolaan Air Limbah Industri Tapioka: Studi Kasus Kabupaten Ciamis, Jawa Barat) - Mochammad Chaerul; Astried Sunaryani (Jurnal Manusia dan Lingkungan, 2014)
ABSTRACTCiamis district is one of the industrial centers of tapioca starch in West Java. Industry has been utilizing solid waste into by-products, fertilizers and animal feeds, but the wastewater which consist a lot of organic substances still discharged directly into the water that potentially cause water pollution. This study aims to determine the wastewater treatment system that can be applied in tapioca starch industry based on five scenarios proposed by using fuzzy goal programming approach. The first objective is the achievement of stream standard (DO-dissolved oxygen and BOD-biochemical oxygen demand) and wastewater quality standards. The second objective is to minimize the cost of wastewater treatment. Wastewater treatment system that proposed, consists of a primary, secondary and collective treatment that shared by some of the industries in one segment with 20% efficiency of BOD removal for primary, 60% for secondary and 85% for collective treatment. The results show that scenario five, which consists of primary, secondary and collective wastewater treatment is chosen for all industries by considering economic and environmental aspects. There was some improvement of water quality for the Cijolang middle-stream segment with DO 7.35 mg/L and BOD 3.68 mg/L; Citanduy middle-stream segment with DO 6.24 mg/L and BOD 2.37 mg/L, and also for Citanduy down-stream segment  with DO 6.11 mg/L and BOD 5.52 mg/L. The fulfillment of BOD pollutant load limits obtained with achieving BOD concentration of 6.32 to 27.89 mg/L of each industry with total cost incurred is IDR 62,689 per day. Fuzzy goal programming approach provides a solution in achievement and as useful information for decision-makers to improve the quality of the environment, especially in the district of Ciamis.ABSTRAKKabupaten Ciamis merupakan salah satu sentra industri tapioka di Jawa Barat. Industri tapioka menghasilkan limbah cair dan limbah padat. Pelaku industri sudah memanfaatkan limbah padat menjadi produk samping, pupuk dan makanan ternak, namun limbah cair belum diolah dengan baik dan masih dibuang langsung ke badan air yang berpotensi menimbulkan pencemaran air sungai. Penelitian ini mengkaji sistem pengolahan air limbah yang dapat diterapkan di industri tapioka berdasarkan atas lima skenario yang diusulkan melalui pendekatan fuzzy goal programming dengan sasaran untuk memenuhi baku mutu DO (dissolved oxygen) dan BOD (biochemical oxygen demand) air sungai, baku mutu limbah yang telah ditetapkan dan minimalisasi biaya pengolahan. Tiga sistem pengolahan air limbah terdiri atas pengolahan air limbah tingkat I, tingkat II dan pengolahan kolektif yang dipakai bersama dalam satu segmen sungai dengan efisiensi penyisihan BOD 20% untuk pengolahan tingkat I, 60% untuk tingkat II dan 85% untuk pengolahan kolektif. Dari hasil penelitian, skenario kelima yang merupakan rangkaian dari pengolahan primer, sekunder dan kolektif memberikan hasil yang paling baik dengan perbaikan kualitas perairan untuk segmen Sungai Cijolang tengah dengan DO 7,35 mg/L dan BOD 3,68 mg/L; untuk segmen Sungai Citanduy tengah dengan DO 6,24 mg/L dan BOD 2,37 mg/L; dan untuk segmen Sungai Citanduy Hilir dengan DO 6,11 mg/L dan BOD 5,52 mg/L. Pemenuhan batas beban pencemar BOD diperoleh dengan pencapaian konsentrasi BOD sebesar 6,32 – 27,89 mg/L dari setiap industri. Dan biaya minimal yang dikeluarkan adalah sebesar Rp 62.689 per hari. Pendekatan fuzzy goal programming dapat memberikan suatu solusi dalam pencapaian sasaran dan merupakan sebuah informasi yang bermanfaat bagi pengambil keputusan untuk meningkatkan kualitas lingkungan khususnya di Kabupaten Ciamis.